PROFIL KETERAMPILAN PEMECAHAN MASALAH SISWA SMA NEGERI 1 WONOMULYO PADA MATA PELAJARAN BIOLOGI DI MASA PANDEMI COVID-19 - Siti Rahmawati; Abd Muis (Universitas Cokroaminoto Palopo, 2022)
This research to describe problem solving skills on the biology subject of SMA Negeri 1 Wonomulyo students during the pandemic Covid-19. Descriptive research with this survey method uses the sampling is simple random sampling. Research subjects in research these are students of class X MIPA which consists of 5 classes and each class represented by 11 people, so the research subjects amounted to 55 people. Collecting data in this study using skills test questions essay problem solving, structured interview with eye teacher biology lessons and documentation of lesson plans and questions used by teachers which aims to serve as information supporting research results. Result data the study was analyzed using descriptive statistical analysis for describe students' problem solving skills, as well as analysis using the excel program to calculate the average of each indicator problem solving skills . The results showed that the four indicator of problem solving skills the highest percentage obtained indicator planning problem solving 60.45%; and lowest percentage indicator that is solving the problem 32.95%. Overall skill problem solving for SMA Negeri 1 Wonomulyo students is in the less category with an average of 48.52